How do animal performance and methane emissions vary with forage management intensification and supplementation? - Koscheck, J. F.W.; Romanzini, E. P. [UNESP]; Barbero, R. P.; Delevatti, L. M. [UNESP]; Ferrari, A. C. [UNESP]; Mulliniks, J. T.; Mousquer, C. J.; Berchielli, T. T. [UNESP]; Reis, R. A. [UNESP] (CSIRO Publishing, 2020)
Context: Yields from Brazilian beef-production systems do not always match the expected potential of a forage-based beef-production system. This efficiency is dependent on adjustments of grazing intensity and supplement utilisation to achieve higher bodyweight gain and lower methane emission. Therefore, more studies are necessary to evaluate the association between pasture management and supplement doses. Aims: The aim of the present study was to determine nutrient intake, nutrient digestibility, animal performance, carcass characteristics and enteric methane emissions of young Nellore bulls grazing Urochloa brizantha cv. Marandu pastures. Methods: One hundred and forty-eight yearling bulls (230 ± 17 kg) were randomly assigned to a grazing-by-supplementation strategy that was designed to allocate three different sward heights with differing levels of supplementation during the wet season. Treatment combinations were (1) low sward height with high supplementation (LH-HS, 15-cm sward height and supplementation at 0.6% of bodyweight (BW)); (2) low height with moderate supplementation (LH-MS, 15 cm and 0.3% BW); (3) moderate height with moderate supplementation (MH-MS, 25 cm and 0.3% BW); (4) moderate height with low supplementation (MH-LS, 25 cm and 0.1% BW); (5) high height with low supplementation (HH-LS, 35 cm and 0.1% BW); and (6) high height with no supplementation (HH-WS, 35 cm). Key results: Bulls in the HH groups had a greater herbage intake than did those in the LH groups (P < 0.01). Bulls in the LH-HS treatment resulted in a greater (P < 0.01) carcass average daily gain than that obtained with LH-MS, MH-LS or HH-WS treatment. Higher stocking rate with the LH treatment resulted in greater gains per hectare in terms of both BW and carcass (P < 0.01). Carcass yield was greater for bulls maintained with the LH-HS treatment (54.3% BW). Higher enteric methane emissions were observed from bulls under the HH treatments (P < 0.01). Conclusions: Comparing carcass gains per hectare and low methane emissions, the present study indicated that pasture management towards a low sward height combined with 0.3% or 0.6% BW supplementation can result in a greater nutrient utilisation efficiency of bulls. Implications: Results provided information to obtain better gains per animals and area, also decreasing methane emission of beef cattle production system.
Keywords: beef cattle; carcass; greenhouse gas; tropical pastures